Tinjauan Ekonomi Syariah Terhadap Penggunaan E-Wakaf Serta Perannya Dalam Mendorong Generasi Muda Berwakaf - ‘Ula, Tajul; Alwin Abdillah, Muhammad (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2023)
The potential of waqf as one of the asset instruments of Muslims in Indonesia has a great opportunity in sustainable economic development in the era of rapid technological development. These potentials and opportunities prompted this research to be carried out with the aim of knowing the perspective of Sharia economic law on collecting cash waqf funds through the use of Fintech or what is familiarly called E-Waqf. Furthermore, how this application encourages the interest of the younger generation in waqf and the factors that influence it. This article is classified as a literature research with a qualitative approach as the basis. The methodology used is a juridical-normative study for the review of E-Waqf law, and a qualitative method in mapping the interest of millennials in waqf. The results of this study show that the use of E-Waqf in waqf is allowed with several conditions that must be met. Meanwhile, the interest of the younger generation in waqf through E-Waqf is still relatively low. This is due to the lack of trust of the younger generation in waqf institutions that manage waqf assets